Application of Simple Additive Weighting Method in Choosing the Best-Selling CCTV Based on Website - Sitohang, Hotmian; Damaini, Amaya Andri (Department of Information Technology, Universitas Timor, Indonesia, 2024)
As crime increases, such as theft, murder, and accidents make it difficult for people to find out who the perpetrators are. With the development of technology, the above problems are easily revealed if the scene is equipped with Closed Circuit Television (CCTV). However, currently there are many types of CCTV models sold on the market, making people confused about choosing which one is good. Likewise, sellers have difficulty in stocking CCTV. This problem requires an application and SAW method to select the best-selling CCTV. The application is built web-based using visual studio code software and the Xampp database. Where later this algorithm can add up the weighted performance ratings on each alternative with ranking. All attributes can be completed simply, so that the best-selling product is obtained. From the results of the study, the best-selling CCTVs were the hikvision, yosse with, and V380 brands.